2023
DOI: 10.31910/rdafd.v9.n1.2023.2308
|View full text |Cite
|
Sign up to set email alerts
|

Carga de entrenamiento y respuesta psicológica de futbolistas en aislamiento por Covid-19

Abstract: Introducción: la evidencia sobre la relación entre carga de entrenamiento y aspectos psicológicos en el aislamiento por la pandemia de la COVID-19 es escasa y se requieren estudios orientados a prevenir lesiones deportivas en el fútbol competitivo. Objetivo general: determinar la carga de entrenamiento y su relación con la respuesta psicológica de futbolistas profesionales, durante el confinamiento por la pandemia COVID-19. Materiales y métodos: diseño observacional, descriptivo-correlacional, se valoraron 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Eight studies ( Mon-López et al, 2020 ; Aghababa et al, 2021 ; Han et al, 2021 ; Kesilmis et al, 2021 ; Villaseca-Vicuña et al, 2021 ; Wagemans et al, 2021 ; Montealegre-Mesa et al, 2023 ) assessed the mood swings of soccer athletes during the COVID-19 pandemic. Aghababa et al (2021) found that due to the psychosocial situation of the COVID-19-related lockdown, the maintenance and execution of unique patterns of physical activity were not compensatory to the point of producing positive effects and changes in the mood states of soccer athletes ( Aghababa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies ( Mon-López et al, 2020 ; Aghababa et al, 2021 ; Han et al, 2021 ; Kesilmis et al, 2021 ; Villaseca-Vicuña et al, 2021 ; Wagemans et al, 2021 ; Montealegre-Mesa et al, 2023 ) assessed the mood swings of soccer athletes during the COVID-19 pandemic. Aghababa et al (2021) found that due to the psychosocial situation of the COVID-19-related lockdown, the maintenance and execution of unique patterns of physical activity were not compensatory to the point of producing positive effects and changes in the mood states of soccer athletes ( Aghababa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cruz (1997) referred to a triad of agents participating in the well-being and performance of athletes: the coaching staff, the athletes themselves and their families (Águila & Padilla-Cazorla, 2022). By implementing comprehensive interventions involving these three parties, it is possible to create a context that promotes adherence to physical exercise, even during emotionally complex stages such as adolescence (Jewett et al, 2019;Montealegre-Mesa, 2023). During this developmental period, physical activity often decreases, leading to potential sports dropout as adolescents prioritize other activities.…”
Section: Introductionmentioning
confidence: 99%